THE INFLUENCE OF LEADERSHIP ON EMPLOYEE MOTIVATION - de Moura, Débora Ediele Machado; Matte, Juliana; Machado, Vanessa de Campos; da Costa, Luana Folchini; Miri, Daniel Hank; Chais, Cassiane; Ganzer, Paula Patricia; Olea, Pelayo Munhoz (Seven Editora, 2025)
The figure of the leader has become indispensable in organizations, as leaders can encourage their teams to strive for excellence, innovate, and create new ways of carrying out activities, managing unforeseen situations with calmness and creativity, and influencing people to achieve both their own goals and those of the organization. For these factors to occur, it is necessary that all those involved are motivated. Therefore, this study aims to understand, from the perspective of subordinates, how leadership influences the motivation of team members in a company within the metallurgical sector in Caxias do Sul, Rio Grande do Sul, Brazil. Regarding methodology, a questionnaire was administered to 69 employees from the administrative area of a company that manufactures machinery and equipment for the beverage, food, and chemical industries, in order to assess the level and orientation of motivation, as well as the leadership style perceived by subordinates. The results revealed that most respondents exhibit a high level of motivation and a success-oriented profile. In addition, their leaders demonstrate an integrative leadership style. On the other hand, it was identified that gender, length of service, and average salary do not statistically significantly influence employee motivation. DOI: https://doi.org/10.56238/sevened2025.036-137